The involuntary nature of binge drinking: goal directedness and awareness of intention. (16th April 2017) - Doñamayor, Nuria; Strelchuk, Daniela; Baek, Kwangyeol; Banca, Paula; Voon, Valerie
Abstract: Binge drinking represents a public health issue and is a known risk factor in the development of alcohol use disorders. Previous studies have shown behavioural as well as neuroanatomical alterations associated with binge drinking. Here, we address the question of the automaticity or involuntary nature of the behaviour by assessing goal‐directed behaviour and intentionality. In this study, we used a computational two‐step task, designed to discern between model‐based/goal‐directed and model‐free/habitual behaviours, and the classic Libet clock task, to study intention awareness, in a sample of 31 severe binge drinkers (BD) and 35 matched healthy volunteers. We observed that BD had impaired goal‐directed behaviour in the two‐step task compared with healthy volunteers. In the Libet clock task, BD showed delayed intention awareness. Further, we demonstrated that alcohol use severity, as reflected by the alcohol use disorders identification test, correlated with decreased conscious awareness of volitional intention in BD, although it was unrelated to performance on the two‐step task. However, the time elapsed since the last drinking binge influenced the model‐free scores, with BD showing less habitual behaviour after longer abstinence. Our findings suggest that the implementation of goal‐directed strategies and the awareness of volitional intention are affected in current heavy alcohol users. However, the modulation of these impairments by alcohol use severity and abstinence suggests a state effect of alcohol use in these measures and that top‐down volitional control might be ameliorated with alcohol use cessation. Abstract : Model‐based/goal‐directed and model‐free/habitual behaviours and intention awareness were assessed in 31 severe binge drinkers and 35 healthy volunteers. Binge drinkers showed impaired goal‐directed behaviour and delayed intention awareness. Further, alcohol use severity correlated with decreased intention awareness, and the time elapsed since the last drinking binge influenced goal‐directed and habitual behaviours. This modulation suggests a state effect of alcohol use in these measures and that top‐down volitional control might be ameliorated with alcohol use cessation.